IMPLEMENTASI PASAL 184 KUHP TERHADAP PENANGANAN TINDAK PIDANA PENGANIAYAAN YANG SULIT DITEMUKAN BARANG BUKTI (STUDI KASUS DI KEPOLISIAN RESORT MERAUKE) - Nurul Widhanita Y. Badilla (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The main purpose of this research is to find out the implementation of Article 184 of the Criminal Procedure Code on the handling of criminal acts of persecution and the obstacles faced by the Merauke Resort Police in dealing with criminal acts of persecution that are difficult to find evidence of, while the method used in this research is empirical juridical. From the results of the research conducted by the author that the implementation of evidence in the investigation of criminal acts of persecution can be said to be valid to be transferred to the court if there are at least two valid pieces of evidence in accordance with Article 183 and Article 184 of the Criminal Procedure Code. If the existing evidence does not reach two valid pieces of evidence, then the evidence does not have sufficient evidentiary power at trial to prove the truth of the arguments or events or statements put forward. The obstacle for the Merauke Resort Police in dealing with criminal acts of persecution is that it is difficult to find evidence, namely from internal causes and external causes. It is necessary to make additional regulations regarding evidence to be used as a basis in handling or deciding criminal cases, especially regarding the crime of persecution. It is necessary to increase human resources such as the number of personnel and facilities and infrastructure such as rooms or houses for storing state confiscated objects for securing evidence of criminal acts as well as the Merauke Resort Police must firmly provide more explanations to witnesses and suspects the importance of evidence for the criminal investigation process persecution.